ANALISIS SISTEM DISTRIBUSI KABEL BERCABANG DENGAN KABEL KONVENSIONAL DI APARTEMEN ANCOL MANSION - Redaksi Tim Jurnal (Energi & Kelistrikan, 2016)
In this Mansion Apartment Building there is electricity installation that have capacity about 3600 kVA that’s be supplied by main electricity resource namely PLN State Electricity Company and Generator set as reserve source. Low voltage cable distribution system network in order to distribute the power of electricity to building main panel to each floor panel use cable branch system thataccording to developer it is more saver from its investment cost sector and also more efficient from its installation technical and can decrease the apreciate of distribution voltage. This research analyze this building electricity distribution system that have been installed the branch of cable be compared if use conventional cable by method in collecting burden data, the flat and length of cable as suitable with the field. For conventional cable data be made assumption base on burden data, meanwhile the flat and length of cable as suitable with the exist cable. Result of this analysis be gotten the electricity distribution sistem comparison data that use branch of cable more saver for the investment sector and operational method be compared if use conventional cable. The results obtained by analysis of usage data distribution cables on each floor according to the load and cable length shrinkage maximum voltage wires branched 1.64% on the 40th floor, while 2.98% of conventional cables at the floor sama.Susut voltage does not exceed 5% .. Comparison of electrical distribution system use more sparingly branched wiring in investment and operationally than using conventional cables at 24.35%.